2021
DOI: 10.3390/children8040309
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Appendicitis Inflammatory Response Score in Distinguishing Perforated from Non-Perforated Appendicitis in Children

Abstract: Background: This prospective observational study aimed to evaluate the validity of appendicitis inflammatory response (AIR) score in differentiating advanced (perforated) from simple (non-perforated) appendicitis in pediatric patients. Methods: A single-center prospective cross-sectional study was conducted between 1 January 2019 until 1 May 2020 including 184 pediatric patients who underwent appendectomy. Based on the intraoperative finding of advanced (n = 38) or simple (n = 146) appendicitis the patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 27 publications
1
36
0
1
Order By: Relevance
“…Acute appendicitis is the most common condition in the pediatric population that leads to emergency abdominal surgery [1,2]. Although advanced diagnostic imaging is widely available, the initial diagnosis of appendicitis in children can be challenging, with rates of misdiagnosis reaching 100% in children aged two years or younger [3][4][5][6]. This has been attributed to nonspecific presentation and overlap of symptoms with other common Diagnostics 2022, 12, 127 2 of 13 childhood conditions such as mesenteric lymphadenitis, gastroenteritis, or Meckel's diverticulitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute appendicitis is the most common condition in the pediatric population that leads to emergency abdominal surgery [1,2]. Although advanced diagnostic imaging is widely available, the initial diagnosis of appendicitis in children can be challenging, with rates of misdiagnosis reaching 100% in children aged two years or younger [3][4][5][6]. This has been attributed to nonspecific presentation and overlap of symptoms with other common Diagnostics 2022, 12, 127 2 of 13 childhood conditions such as mesenteric lymphadenitis, gastroenteritis, or Meckel's diverticulitis.…”
Section: Introductionmentioning
confidence: 99%
“…This has been attributed to nonspecific presentation and overlap of symptoms with other common Diagnostics 2022, 12, 127 2 of 13 childhood conditions such as mesenteric lymphadenitis, gastroenteritis, or Meckel's diverticulitis. Clinical scores, such as Alvarado, appendicitis inflammatory response score, and pediatric appendicitis score have been developed to aid the diagnosis of acute appendicitis in children [3,4]. The diagnostic delay often leads to a higher incidence of complications, such as perforation.…”
Section: Introductionmentioning
confidence: 99%
“…The Alvarado score is a frequently utilized tool for acute appendicitis symptom gradation, yet it lacks specificity and sensitivity [ 19 ]. Recently, Appendicitis inflammatory score (AIR) has been created to overcome shortcomings of the Alvarado score and Pediatric appendicitis score [ 20 ]. Recent studies validated the AIR score and reported that the AIR score significantly outperforms the older Alvarado score, especially in distinguishing simple from advanced appendicitis but still not enough to be exclusive criteria in establishing the diagnosis of acute appendicitis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“… 10 One prospective observational study presented the validity of the AIR score in distinguishing pediatric appendicitis patients with simple and perforated appendicitis with 89.5% sensitivity and 71.9% specificity by using a cut-off value of 9. 11 In contrast to the Alvarado and PAS scores, the AIR score uses CRP as one of the variables in detecting inflammatory response or process. 11 Moreover, recent studies explored the ability of hyponatremia and hyperbilirubinemia as discriminative markers of complicated appendicitis.…”
Section: Introductionmentioning
confidence: 99%
“… 11 In contrast to the Alvarado and PAS scores, the AIR score uses CRP as one of the variables in detecting inflammatory response or process. 11 Moreover, recent studies explored the ability of hyponatremia and hyperbilirubinemia as discriminative markers of complicated appendicitis. However, hyponatremia was studied only in the pediatric population, whereas hyperbilirubinemia was studied in both pediatric and adult patients.…”
Section: Introductionmentioning
confidence: 99%